In Vivo Confocal Microscopy of Conjunctival Roundish Bright Objects: Young, Older, and Sjögren Subjects - Villani, Edoardo; Beretta, Silvia; Galimberti, Daniela; Viola, Francesco; Ratiglia, Roberto (Investigative ophthalmology & visual science, 2011)
To investigate by laser scanning confocal microscopy (LSCM) the density of presumed epithelial, presumed goblet, and presumed inflammatory cells in the tarsal conjunctiva of healthy young and older subjects and in patients with Sjögren's syndrome (SS). To evaluate the interobserver variability and to compare the measured densities with known age-related and SS-related changes. The authors studied 24 eyes of 12 healthy young subjects (8 women, 4 men; average age, 26 years; age range, 21-30 years), 24 eyes of 12 healthy older subjects (10 women, 2 men; average age, 68 years; age range, 67-74 years), and 24 eyes of 12 patients with SS (10 women, 2 men; average age, 62 years; age range, 49-72 years). The inferior tarsal conjunctiva of each patient was examined in vivo by LSCM. The density of the three cell types was independently analyzed by two masked investigators. The density of presumed epithelial, presumed goblet, and presumed inflammatory cells was significantly higher in SS patients than in both control groups (P < 0.001; Mann-Whitney U test). The densities for presumed goblet cells calculated by the two investigators were significantly different from one another (P < 0.01, Mann-Whitney U test) and were not correlated. LSCM is a promising tool that should profoundly change the study of the ocular surface, but it requires accurate standardization before it is used in clinical practice.